Bioactivity of chitosan-based particles loaded with plant-derived extracts for biomedical applications: emphasis on antimicrobial fiber-based systems - Antunes, Joana Isabel Costa (2021)
Marine-derived chitosan (CS) is a cationic polysaccharide widely studied for its bioactivity, which is mostly attached to its primary amine groups. CS is able to neutralize reactive oxygen species (ROS) from the microenvironments in which it is integrated, consequently reducing cell-induced oxidative stress. It also acts as a bacterial peripheral layer hindering nutrient intake and interacting with negatively charged outer cellular components, which lead to an increase in the cell permeability or to its lysis. Its biocompatibility, biodegradability, ease of processability (particularly in mild conditions), and chemical versatility has fueled CS study as a valuable matrix component of bioactive small-scaled organic drug-delivery systems, with current research also showcasing CS's potential within tridimensional sponges, hydrogels and sutures, blended films, nanofiber sheets and fabric coatings. On the other hand, renewable plant-derived extracts are here emphasized, given their potential as eco-friendly radical scavengers, microbicidal agents, or alternatives to antibiotics, considering that most of the latter have induced bacterial resistance because of excessive and/or inappropriate use. Loading them into small-scaled particles potentiates a strong and sustained bioactivity, and a controlled release, using lower doses of bioactive compounds. A pH-triggered release, dependent on CS's protonation/deprotonation of its amine groups, has been the most explored stimulus for that control. However, the use of CS derivatives, crosslinking agents, and/or additional stabilization processes is enabling slower release rates, following extract diffusion from the particle matrix, which can find major applicability in fiber-based systems within ROS-enriched microenvironments and/or spiked with microbes. Research on this is still in its infancy. Yet, the few published studies have already revealed that the composition, along with an adequate drug release rate, has an important role in controlling an existing infection, forming new tissue, and successfully closing a wound. A bioactive finishing of textiles has also been promoting high particle infiltration, superior washing durability, and biological response.